2010
DOI: 10.2174/1874213001003010041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Removal of Garlic Mustard (Alliaria petiolata, Brassicaeae) on Arbuscular Mycorrhizal Fungi Inoculum Potential in Forest Soils

Abstract: Garlic mustard (Alliaria petiolata), a biennial species, is considered to be among the most troublesome of the invasive plants in the Eastern Deciduous forest of North America. It has been shown to prevent or reduce mycorrhizal colonization of native herbaceous ground layer plants and trees in these forests. It is estimated that 70-90% or more of herbaceous native ground layer plant species form associations with arbuscular mycorrhizal fungi (AMF). Loss of the mycorrhizal association can reduce growth, reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Alliaria petiolata, for example, suppresses the growth rates of native tree seedlings by interfering with root infection by arbuscular mycorrhizal fungi (Stinson et al 2006). Alliaria petiolata appears to depress mycorrhizal inoculum potential (Anderson et al 2010;Roberts and Anderson 2001), and it been shown to inhibit seed germination and plant growth (Prati and Bossdorf 2004). Manipulative studies based on the removal of A. petiolata revealed an increase in evenness and ShannonWeiner diversity of forest understory plants (McCarthy 1997;Stinson et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Alliaria petiolata, for example, suppresses the growth rates of native tree seedlings by interfering with root infection by arbuscular mycorrhizal fungi (Stinson et al 2006). Alliaria petiolata appears to depress mycorrhizal inoculum potential (Anderson et al 2010;Roberts and Anderson 2001), and it been shown to inhibit seed germination and plant growth (Prati and Bossdorf 2004). Manipulative studies based on the removal of A. petiolata revealed an increase in evenness and ShannonWeiner diversity of forest understory plants (McCarthy 1997;Stinson et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Disruption of the AMF over multiple growing seasons could have severe impacts on the growth of native herbs, as some native perennials are incapable of maintaining a positive phosphorus budget without their associated AMF (Merryweather and Fitter 1995). However, recent work by Anderson et al (2010) demonstrates that the suppression of AMF can be reversed when garlic mustard is removed for multiple consecutive growing seasons. Sites invaded by garlic mustard may require long-term and intense management to prevent an overall reduction in the abundance of the forest fungal community.…”
Section: Discussionmentioning
confidence: 99%
“…These changes to the abiotic and biotic soil environment may persist as legacy effects. The temporal dynamics of belowground legacy effects following invader removal are poorly understood (but see Anderson et al 2010 andLankau 2011), but inferences can be drawn based on current understanding of the biology of mycorrhizal fungi.…”
Section: Mutualism Recovery Over Time Following Invader Removalmentioning
confidence: 99%